Early Encounters : Native Americans and Europeans in New England. From the Papers of W. Sears Nickerson. - Carpenter, Delores Bird (Michigan State University Press, 1995)
Early Encounters contains a selection of nineteen essays from the papers of prominent New England historian, antiquarian, and genealogist Warren Sears Nickerson (1880-1966). This extensive study of his own family ties to the Mayflower, and his exhaustive investigation of the first contacts between Europeans and Native Americans, in what is today New England, made him an unquestioned authority in both fields. The research upon which the text of Early Encounters is based occurred between the 1920s and the 1950s. Each of Nickerson's works included in this carefully edited volume is placed i.